Description of Resilience in Post-Married Adolescent Adolescent in Sidoarjo: Gambaran Resiliensi Pada Remaja Pasca Berhubungan Seksual Pra Nikah di Sidoarjo - Muhammad Wildan Al Jawahiri; Widyastuti Widyastuti (Academia Open, 2022)
Premarital sexual relations experienced by young women can have a negative psychological impact. To deal with these conditions, it takes skills to restore mental conditions to normal, such as having not been exposed to a problem called resilience. This study aims to determine the description of resilience and the factors that influence resilience in adolescents who have had premarital sex. This study uses a qualitative method with a phenomenological type, using 1 female subject aged between 13 – 23 years who lives in the city of Sidoarjo. Determination of subjects using a non-random sampling technique with purposive sampling strategy, data collection methods in the form of interviews with one primary subject, 2 significant others, and rating scale. The results showed that there was a picture of resilience in adolescent girls who had experienced adversity due to premarital sex. The most dominant aspect is insight, and the aspect that does not appear is humor. As well as showing the factors that influence resilience in adolescent girls in the form of I Have, I Am, I Can.